COLUMNAR REALIZATION AND LIQUIDATION STATEMENT. - Newlove, G. H. (The Accounting Review, 1946)
Abstract As the orthodox realization and liquidation account does not adequately present the affairs of a company under liquidation in bankruptcy or one being reorganized under a receiver, repeated attempts have been made to improve the reporting for such concerns, as of January 1946. Some of these attempts have adapted the ordinary interim work sheet by inserting additional columns so that the trading transactions may be distinguished from the non-trading transactions. The other method of attacking the problem adapts the principles of the articulation statement in that the money amounts involved are sorted into columns according to the types of transactions and sorted to lines according to the titles of the accounts affected. The article presents some general rules for the preparation of columnar realization and liquidation statements. First rule is to classify transactions according to the columnar headings and determine whether the entries should be recorded as debit or credit according to the effect the transactions have in the accounts named on the lines. Also, record all cash collections as realizations of assets and all cash disbursements as payments of liabilities.